Kedudukan Śrī Kṛṣṇa pada Devī Bhāgavata Purāṇa Perspektif acintya-bhedābheda-tattva - I Gusti Ngurah Agung Mahesa Mahaputra (UHN IGB Sugriwa Denpasar, 2018)
evī Bhāgavata and Śrīmad-Bhāgavatam from the theological aspects both affirm Lord Kṛṣṇa as Puruṣa (ancient God). It is something unique that Devī Bhāgavata in the whole of Skanda always position Ādyāśakti asAlmighty God (supreme Brahman and also māyā), but at the same time in Skanda 9, Devī Bhāgavata also confirmed Lord Kṛṣṇa as Puruṣa. In general we know that Durgā or Śakti refers to potential or energy while Śivaor Kṛṣṇa is the source of potential or possessing energy, but in the proposition of Devī Bhāgavata, the Ādyāśaktiacts as Brahman or Puruṣa and at the same time Mahāmāyā. In another narration on Devī Bhāgavatam alsostates that Ādyāśakti as primal śakti (Nirguṇa Brahman) and positions Puruṣa as His instrument